Вплив інгібіторів карбоангідрази на ріст і пігментний склад синьозелених водоростей - Подорванов, В.В.; Назаренко, О.А.; Терещенко, О.Ф. (Український фітоценологічний збірник, 2006)
The effect of carboanhydrase inhibitors acetozolamide (AZ) and ethoxyzolamide (EZ) on the grows and pigment composition of photosynthetic apparatus of cyanobacteria (Spirulina platensis (Norst) Geitl. and Nostoc linckia (Roth.) Born. et Flash.) was studied. It was established that both inhibitors had no effect on biomass production by Spirulina platensis and on content of chlorophyll a and carotenoids. But biomass production by two strains Nostoc linckia, which was found at two opposite slopes of «Evolution Canyon», Mount Carmel Natural Oren, Israel, microclimate of which is very different, was depressed in some extent by 0.1 mM AZ and fully depressed by 0.5 mM EZ. After addition of this inhibitors to the growth medium the content in both strains was greatly altered. There were some differences in the sensitivity of these Nostoc linckia strains to carboanhydrase inhibitors. The mechanisms of these inhibitors action are discussed.